2023
DOI: 10.3390/microorganisms11102429
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Identification and Antifungal Susceptibility of Clinical Isolates of Aspergillus Section Flavi from Three French Hospitals

Elie Djenontin,
Jean-Marc Costa,
Bita Mousavi
et al.

Abstract: (1) Background: Aspergillus flavus is a cosmopolitan mold with medical, veterinary, and agronomic concerns. Its morphological similarity to other cryptic species of the Flavi section requires molecular identification techniques that are not routinely performed. For clinical isolates of Aspergillus section Flavi, we present the molecular identification, susceptibility to six antifungal agents, and clinical context of source patients. (2) Methods: One hundred forty fungal clinical isolates were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…in 2020 2 . All the strains had been identified in a previous study, 22 except strain GRE150, identified in the present study.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…in 2020 2 . All the strains had been identified in a previous study, 22 except strain GRE150, identified in the present study.…”
Section: Methodssupporting
confidence: 67%
“…DNA extraction and molecular identification were performed as previously described 22 . Identification was performed by partial sequencing of the β‐tubulin and calmodulin genes and comparison to the sequence of the type strains of each the cryptic species within the Flavi section based on the most recent taxonomic revision of the Flavi section published by Houbraken et al.…”
Section: Methodsmentioning
confidence: 99%
“…These genes contain conserved sequences common to all fungi; however, for some genera, this target does not allow the identification of all the species that compose it, making it necessary to search for other targets with greater resolving power. Different gene regions, such as beta-tubulin, have been used that show potential for the identification of fungi such as N. crassa and other genera such as Colletotrichum and Aspergillus with DNA sequence analysis [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus section Flavi comprises several species that are frequently found in agricultural crops. Certain species within this section can produce aflatoxins (Podgórska-Kryszczuk, 2023), while others are known to cause aspergillosis and respiratory allergies in humans (Djenontin et al, 2023). Aspergillus flavus, one of the most significant species in this section, is a major producer of aflatoxins (Bertechini-Faria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A. flavus is a species that presents challenges due to its capacity to grow on diverse substrates in varying environmental conditions and produce numerous spores that can survive under extreme circumstances (Segura-Palacios et al, 2021). It is frequently found in tropical and subtropical regions where the temperature ranges from 28-37°C and the relative humidity is above 85% (Okayo et al, 2020;Djenontin et al, 2023). This species is commonly found in crops such as maize, soybean, peanuts, pistachios, cottonseed, sunflower seeds, and rice (Douksouna et al, 2019;Segura-Palacios et al, 2021).…”
Section: Introductionmentioning
confidence: 99%